Rubber Agriculture Tapanuli in the Malaise Era, 1929 – 1939 - Edi Sumarno; Junita Setiana Ginting; Nina Karina; M. Azis Rizky Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Entering the early 1930s, people's purchasing power has decreased due to the sluggish world economy. This event was later called "The Great Depression" or better known as "Malaise". This decline also occurred in the automotive industry sector which uses a lot of processed rubber as a supporting component. Reduction of the amount of production in the automotive industry then results in reduced absorption of processed rubber . At the same time, the production of rubber precisely increased. As a result, the price of rubber has dropped dramatically. This condition has certainly hit rubber producers. Including smallholder rubber farmers in Tapanuli who also felt the impact of the economic crisis. This paper discusses the condition of smallholder rubber farming in Tapanuli during the malaise. The discussion starts from the situation of smallholder rubber farming before the malaise, continued with the economic depression and its impact on rubber prices, the policy of production restriction by the Dutch East Indies Government and its application, to the impact on rubber farmers in the region. From the results of this study, it can be said that smallholder rubber farmers in Tapanuli were also affected by the "malaise" but the impact was not significant because the community did not adopt a monoculture pattern.